2010
DOI: 10.28945/1295
|View full text |Cite
|
Sign up to set email alerts
|

Real World Project: Integrating the Classroom, External Business Partnerships and Professional Organizations

Abstract: Executive SummaryA college degree is not what it used to be in respect to securing future employment. Constantly changing technologies in a struggling economy make it necessary for organizations to carefully balance recruitment staffing, particularly with regards to new hires. Organizations want to know that each new hire can add value immediately. In order to add value, Information Systems (IS) graduates must possess the necessary technical skills as well as "real world" work experience and soft skills. Addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…This gave them a much greater appreciation for the task of procuring software than just reading about it in textbooks. The educational benefits of using realworld projects are well established both in the United States (Grant et al, 2010) and internationally (Magboo and Magboo, 2003).…”
Section: Insights For the Sad Coursementioning
confidence: 99%
“…This gave them a much greater appreciation for the task of procuring software than just reading about it in textbooks. The educational benefits of using realworld projects are well established both in the United States (Grant et al, 2010) and internationally (Magboo and Magboo, 2003).…”
Section: Insights For the Sad Coursementioning
confidence: 99%
“…A theoretical and practical misalignment in cultivating workplace readiness and global citizenship in students exists because partnerships are not being optimized between stakeholders. Embedding higher education curriculum with authentic projects from reallife clients is a powerful strategy with far-reaching impacts (Grant et al, 2010). The literature has suggested that administrators, faculty, students, industry, community groups as well as local, state and federal government agencies all benefit from partnerships, as they directly influence political, social, and economic prosperity of communities (Lapan, Osana, Tucker, & Kosciulek, 2002;Manning, 2013).…”
Section: Problem Of Practicementioning
confidence: 99%
“…When students are engrossed in projects with real clients, they work harder to develop creative solutions which further hone marketable skills and increases motivation (Grant et al, 2010;Smith & Gibson, 2016). Students gain a sense of accomplishment through projects, thereby enhancing confidence in their abilities which can be capitalized upon during job interviews (Jacobson, 2001;Rogers, 2014).…”
Section: Experiential Education Through Project-based Learningmentioning
confidence: 99%
See 2 more Smart Citations